2020
DOI: 10.1111/geb.13119
|View full text |Cite
|
Sign up to set email alerts
|

Salty, mild, and low plant biomass grasslands increase top‐heaviness of invertebrate trophic pyramids

Abstract: Aim: Multiple hypotheses predict how gradients of nutrient availability, plant biomass, and temperature shape trophic pyramids. We aim to disentangle the simultaneous influence of those factors and their indirect effects on trophic structure and individual trophic levels. Location: United States. Time period: 2017. Major taxa studied: Invertebrates. Methods: To examine differences in trophic pyramid shape and abundance within trophic levels and across ecological gradients, we conducted 54 standardized surveys … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 69 publications
1
30
0
Order By: Relevance
“…The only non‐grasshopper taxa to vary in abundance with year was the parasitoid Hymenoptera, which had higher abundances in 2019. This response may be due to higher growing season precipitation resulting in more plant aboveground biomass, and thus more habitat volume and our nectar for parasitoids (Post et al., 2000; Welti, Kuczynski, et al., 2020). Generally, non‐grasshopper taxa were only categorized to broad functional‐taxonomic groups and may vary compositionally in response to grazing lawns and drought at finer taxonomic levels.…”
Section: Discussionmentioning
confidence: 99%
“…The only non‐grasshopper taxa to vary in abundance with year was the parasitoid Hymenoptera, which had higher abundances in 2019. This response may be due to higher growing season precipitation resulting in more plant aboveground biomass, and thus more habitat volume and our nectar for parasitoids (Post et al., 2000; Welti, Kuczynski, et al., 2020). Generally, non‐grasshopper taxa were only categorized to broad functional‐taxonomic groups and may vary compositionally in response to grazing lawns and drought at finer taxonomic levels.…”
Section: Discussionmentioning
confidence: 99%
“…While one long-term study of flying insects in the Netherlands found no evidence of higher rates of decline in larger species over the past two decades (Hallmann et al, 2020), larger-bodied species may have become rare earlier in the last century (Seibold et al, 2015). Climate and land-cover change may otherwise alter insect communities by favoring particular trophic levels (Welti, Kuczynski, et al, 2020), invasive (Ju et al, 2017), or pest species (Bernal & Medina, 2018). The lack of an overall unimodal relationship temperature may be a result of the coarse taxonomic (flying insects) and temporal (~2 week) sample resolution in comparison to other studies (e.g.…”
Section: Caveatsmentioning
confidence: 99%
“…One consequence of this dynamic is that herbivores are often sodium limited—with shortfall leading to decreases in growth, survival, performance, and reproduction. This is true for both vertebrate and invertebrate herbivores (Jones and Hanson 1984, Hellgren and Pitts 1997, Welti et al 2019 b , 2020, Kaspari 2020). Invertebrate herbivores sate their sodium needs by puddling (Molleman 2010), opportunistic carnivory (Simpson et al 2006, Clay et al 2017), and seeking out more sodium‐rich plant tissue and exudates (Welti et al 2019 b , Kaspari et al 2020).…”
Section: Introductionmentioning
confidence: 99%